2002
DOI: 10.1128/jb.184.3.679-686.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deletion of Genes Encoding Fe-Only Hydrogenase of Desulfovibrio vulgaris Hildenborough on Hydrogen and Lactate Metabolism

Abstract: The physiological properties of a hyd mutant of Desulfovibrio vulgaris Hildenborough, lacking periplasmic Fe-only hydrogenase, have been compared with those of the wild-type strain. Fe-only hydrogenase is the main hydrogenase of D. vulgaris Hildenborough, which also has periplasmic NiFe-and NiFeSe-hydrogenases. The hyd mutant grew less well than the wild-type strain in media with sulfate as the electron acceptor and H 2 as the sole electron donor, especially at a high sulfate concentration. Although the hyd mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 26 publications
4
79
1
3
Order By: Relevance
“…To specify the importance of this enzyme, the effect of oxygen was also studied on a mutant strain, D. vulgaris HYD100, in which the gene encoding for this hydrogenase had been deleted (27). Changes in total hydrogenase activity and cytochrome content of HYD100 cells, induced by the presence of oxygen, were followed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To specify the importance of this enzyme, the effect of oxygen was also studied on a mutant strain, D. vulgaris HYD100, in which the gene encoding for this hydrogenase had been deleted (27). Changes in total hydrogenase activity and cytochrome content of HYD100 cells, induced by the presence of oxygen, were followed.…”
Section: Resultsmentioning
confidence: 99%
“…This hydrogenase activity rise was related to an increase in the [Fe] hydrogenase is a key enzyme for the dissimilatory sulfate reduction. Its physiological function has been shown to be hydrogen uptake when both hydrogen and lactate are electron donors for sulfate reduction (27) and hydrogen production with pyruvate and lactate as electron donors in the absence of sulfate (37). In vitro experiments have shown that hydrogenases are oxygen-sensitive enzymes (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogenases are ubiquitous in prokaryotes and serve as intermediaries in numerous pathways involved in hydrogen production and/or consumption. Hydrogenases are classified into two metalloenzyme families based on the metal content of the active site: the Ni-containing hydrogenases (i.e., 19,20 .…”
Section: Online)mentioning
confidence: 99%
“…This type of enzyme is found in anaerobic prokaryotes, such as clostridia and sulfate reducers (reviewed by Adams, 1990;Atta andMeyer, 2000 and) and in eukaryotes (Akhmanova et al, 1998;Horner et al, 2000Horner et al, , 2002Florin et al, 2001, Wünschiers et al, 2001b, Happe and Kaminsky, 2002Voncken et al, 2002;Forestier et al, 2003 (Pohorelic et al, 2002). Recently, components of an [FeFe]-H 2 ase have been found associated with formate dehydrogenases from Eubacterium acidaminophilum (Graentzdoerffer et al, 2003).…”
Section: The H 2 -Evolving Energy-conserving Membrane-associated Hymentioning
confidence: 99%